Pengaruh Proteksi Aldehid Untuk Meloloskan Poly Unsaturated Fatty Acid Pada Menir Kedelai dan Minyak Ikan Lemuru Secara In Vitro - Riyanto, Joko (Program Studi Peternakan, Fakultas Pertanian, Universitas Sebelas Maret, 2015)
This research was aims to determine the effect of formaldehyde using as a protective material in the soy groats and lemuru fish oil mixtured to escape of the protein and poly unsaturated fatty acid (PUFA) by in vitro. The rumen fluid was derived from donor of the Ongole crosbred fistulated as much as 3 heads. The experimental design used completely randomized design factorial 2x3 pattern consists of two factors:the first factor (soybean groats:lemuru fish oil in the ratio 2:1 and 4:1) and the second factor (the use of formaldehyde at levels of 0%, 2% and 4% base on the dry matter) and was repeated 5 times. The parameters are consist of the nutrient content, the substrates soybean groats and lemuru fish oil the rumen fluid fermented PUFA content by in vitro. Results of the study are levels of protein, fatty acids oleic, linoleic and arachidonic much available on soybean groats:lemuru fish oil protected formaldehyde at levels of 2% and 4%. The difference between the ratio of soybean groats with lemuru fish oil had no significant (P≥0,05) but significantly different at different levels of formaldehyde (P≤0,05). The conclusion are formaldehyde content of 37% with a level of 2% can be used for protection the soybean groats and lemuru fish oil with a ratio of 4:1 and is able to provide protein as well PUFA